Evidence-Based Medicine and General Practice (International Journal of Food and Nutritional Sciences, 2022)
Clinical decision making, even in primary care, is aided by evidence-based medicine (EBM). One distinguishing feature of general practise is the link between doctor and patient, as well as biological, individual, and environmental factors in making a diagnosis. The vast majority of GP evidence is biomedical in nature and is therefore often not directly applicable to primary care because it is derived from secondary or tertiary settings. A reductionist approach that ignores the broader context of general practise in favour of the biomedical domain and the randomised controlled trial (RCT) is reflected in this focus. Patient treatment should continue to incorporate a balance of context, narrative, patient accounts of sickness, and personal experience with high-quality, relevant research findings.